Induced Sputum for the Investigation of Airway Inflammation: Evidence for Its Clinical Application - Frederick E Hargreave (Canadian Respiratory Journal)
Airway inflammation is considered to be the primary cause of airway diseases. Its prevention and reversal are the primary aims of treatment. Measurement of the inflammation is now possible relatively noninvasively and reliably by using induced sputum cell counts. The differential count indicates the presence and type of the inflammation (eosinophilic or neutrophilic) and the total cell count the intensity. Sputum eosinophilia responds to treatment with corticosteroid, while there is increasing evidence that an isolated neutrophilia does not. Clinical judgement of airway inflammation is made difficult because of the different types of inflammation and their inconsistent correlation with the clinical features. Hence, reliable measurement of induced sputum cell counts may be useful to guide treatment in clinical practice. Consideration should now be given as to how to make it more available.